ENERGY ISSUES AS THE TRIGGER OF FORMATION OF AN INTERNATIONAL REGIME OF THE CASPIAN SEA - I. S. Rozhkov (Vestnik MGIMO-Universiteta)
The research object of the article is a development of the international regime of the Caspian Sea after the collapse of the Soviet Union in 1991 and increase in the number of the Caspian Littoral States, which transformed the former “closed” Soviet-Iranian region to the arena for wrangling between the different foreign policy interests of the most powerful world nations. The research subject is the key role of energy resources in the negotiation process between the States of the Caspian Region. The author pays special attention to the evolution of national approaches of the “Caspian Five” to the problem of mineral resources delimitation as well as its connection to negotiations on the draft comprehensive Convention on the Legal Status of the Caspian Sea. The article mentions the key benchmarks of the negotiation process, examines the influence of biand multilateral arrangements among Russia, Kazakhstan and Azerbaijan during 1998-2003 on the situation in the region. The role of conflicts among Azerbaijan, Iran and Turkmenistan over transboundary oil and gas fields in the southern part of the sea as a factor of regional instability as well as its negative influence on the relations between the Caspian Littoral States, in general, are analyzed. The main conclusion of the author is that debates, launched by the Caspian Littoral States on the energy issues in the format of the Special Working Group at the level of Deputy Foreign Ministers, have gradually transformed to the multilateral mechanism for interaction of regional actors and become a trigger for debates on the other issues of the Caspian agenda such as economic, ecological, military, security, transport, tourist cooperation, etc. Taking into account importance and a positive role of four Caspian Summits as well as influence of other factors (separate position of Iran, external forces, environmental risks) on the negotiation process, the author underlines the fact that all efforts of the Caspian Littoral States should be focused on elaborating the compromise settlement scheme of mineral resources delimitation, which should be fixed in the future comprehensive Convention.